UPDATE ON THE RELATIONSHIP BETWEEN VITAMIN D AND DEPRESSION: SYSTEMATIC REVIEW - Fitriana, Ilma; Intan Permatasari, Dela (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Introduction: Depression remains a significant global health challenge, affecting approximately one in ten individuals, and its multifaceted nature requires prolonged therapeutic interventions. Recent studies have explored the potential link between vitamin D deficiency and depression, highlighting the role of vitamin D in neurobiology and its plausible association with depressive symptoms. However, the exact nature of this relationship and its implications for depression management require further investigation, as outlined in the systematic review "Association of Vitamin D and Depression: An Update Systematic Review," aiming to provide clarity on the role of vitamin D in depression etiology and guide future research and clinical interventions.  Method: The researchers in this study followed the 2020 Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines to ensure that their work met the required standards. This was done to ensure the precision and reliability of the conclusions derived from the research. Result: Our search produced 13 results. After looking at the titles and summaries, we found 10  papers that fit our criteria. At first, we excluded several articles because they were written in review style and case reports. But after reading the full papers carefully, we included five papers in our final analysis. These papers included experimental study, observational study  a randomized, double-blind, placebo controlled clinical trial, a cross-sectional analysis, and  double-blind randomized clinical trial. Conclusion: Some studies indicate improvements in mood, reductions in corticosterone levels, and prevention of serum vitamin D decreases with vitamin D and SSRI antidepressant combination. Another study in obese women with depression showed positive effects on mood, BDNF levels, inflammation, and SIRT1 with vitamin D and magnesium supplementation. However, no significant associations were found between baseline vitamin D levels and depression symptoms, and vitamin D supplementation did not improve depression symptoms in deficient but otherwise healthy individuals, suggesting caution in using it for depression management. Further research, especially in diverse populations, is needed to clarify the role of vitamin D in depression.